Identification of novel therapeutic candidates to treat autoimmune diseases - Lim, Eugene Hui Kiat (2018)
One of the hallmarks of autoimmune diseases is that they are driven by the development of systemic inflammation through microbial infections. Inflammatory responses are controlled mainly by the signaling pathway of the immune adaptor proteins in response to a broad range of human pathogens. By targeting the immune adaptors, we can effectively regulate the activation signals propagated to the inflammasome. Due to the wide range of compound library available, it has been demonstrated in various fields that high-throughput screening of libraries can be conducted to discover new drug leads for biological targets. Therefore, an inhibition screen of NDL-3000 Natural derivative library and synthesized peptides were conducted with an optimized protein oligomerisation assay using selected immune adaptors, MAVS CARD and ASC PYD. Preliminary screening showed that compound pool 6 demonstrated potential inhibitory effects on the oligomerisation of MAVS CARD proteins whereas compound pools 33 and 48 displayed potential enhancement effects to the MAVS CARD oligomerisation. Peptide screening on ASC PYD proteins oligomerisation also showed promising results at 500μM, where the oligomerisation of monomers observed drastically decreased. However, the mechanism of interactions is still unclear, and is a potential area for future research of this field.